Effect of evaporation rate for the heat and mass transfer of the laminar liquid falling film in still air - Du, Yongcheng; Wang, Shiyao; Li, Dongzhen; Peng, Youshun; Yang, Li (Frontiers in Energy Research, 2022)
The heat and mass transfer process of the laminar falling liquid film along a vertical heated plate with constant heat flux is studied. Through thermal equilibrium analysis, the energy conservation equation is established and solved by the parametric variation method. The analytical solution considering evaporation is in good agreement with the experimental results. Based on the model, the temperature distribution of liquid film with or without evaporation is obtained. It is demonstrated that the thickness and average temperature of liquid film show decreasing and increasing trends linearly in the flow direction. Along with the increase in the evaporation rate, the average temperature decreases and the share of evaporative heat dissipation in the total heat flux increases, which demonstrates that evaporation is an important physical factor for heat dissipation when the falling liquid film flows on a hot plate.